Johson The Language instinct. (Economist, 2023)
The article discusses the debate surrounding acquisition of language by humans and role of artificial intelligence particularly language models like ChatGPT in understanding human language. Topics discussed include argument of linguist Noam Chomsky over distinct human language from forms of communication, theories of Chomsky that have been influential in field of syntax, and importance of human brain's innate tendencies for language acquisition.